2011
DOI: 10.1007/s12103-011-9109-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disaggregated Trajectories of Status Offenders: Does CINS/FINS Status Prevent Male and Female Youth From Becoming Labeled Delinquent?

Abstract: This study sought to provide a more recent and longitudinal examination of the effect of formal processing on status offenders' subsequent delinquency using data from a large sample of first-time referral status offenders in the state of Florida. Results from semi-parametric group-based trajectory models suggested that roughly half of the status offenders subsequently accumulated delinquent arrests in adolescence following their initial referral for a status offense. Furthermore, the number and type of traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…In line with previous research conducting female-only analyses of a justice-involved sample (e.g., Blokland & van Os, 2010; Cauffman et al, 2015; 2 Jennings, 2011), the current study revealed a substantial (23.3%) subset of women whose offending continued at a high rate through emerging adulthood (the SRC trajectory). This contrasted with dominant theoretical explanations (e.g., Moffitt, 1993) and studies using mixed samples, which implied that chronic offending was primarily a male-only phenomenon (Corrado et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In line with previous research conducting female-only analyses of a justice-involved sample (e.g., Blokland & van Os, 2010; Cauffman et al, 2015; 2 Jennings, 2011), the current study revealed a substantial (23.3%) subset of women whose offending continued at a high rate through emerging adulthood (the SRC trajectory). This contrasted with dominant theoretical explanations (e.g., Moffitt, 1993) and studies using mixed samples, which implied that chronic offending was primarily a male-only phenomenon (Corrado et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…These youth had the least problematic offending pattern in adolescence, and offending at age 23 was virtually nonexistent. This aligned with studies that reported an AL-type trajectory (e.g., Jennings, 2011). Several trajectory studies using justice-involved samples identified a "low" trajectory (e.g., Cauffman et al, 2015), which was not identified in the present study.…”
Section: Female Offending Patternssupporting
confidence: 89%
See 1 more Smart Citation
“…This shaping process includes specifying the age of onset of crime and desistence from crime, and the analysis of early or late onset and desistence trajectories. Trajectory analysis adds to this approach the observation that the criminal life course can be divided into trajectories or pathways of development that reflect periodic offending, persistent offending, and early and late onset offending patterns among others (Jennings, 2010;Jennings, maldonado-molina, and komro, 2010). in this chapter we draw from the concepts and perspectives developed in criminological life course analysis related to turning points and trajectories to explore the relevance of this approach for examining the life course of chemical pollutants in the environment as an issue relevant to green criminology.…”
Section: P R O O F C O P Ymentioning
confidence: 99%
“…For example, the inclusion criteria for simple assault have changed (now including family disputes), zero-tolerance policies in schools have led to an increase in officially recoded offenses, and in addition there have been local law enforcement changes resulting in the lowering of the thresholds for recording assault and aggravated assault (e.g., [4]). Zahn et al [4] also showed, based on national statistics, that the gender gap in delinquency when counting arrests has narrowed in the past decades, although this is more evident from official records than from self-reported delinquency (also see [5,6]).…”
Section: Introductionmentioning
confidence: 99%